2010
DOI: 10.1007/s11250-010-9701-4
|View full text |Cite
|
Sign up to set email alerts
|

Normal bacterial flora from vaginas of Criollo Limonero cows

Abstract: In order to describe the normal bacterial flora in vaginas of Criollo Limonero cows, 51 healthy multiparous cows, at least 90-day postpartum, were selected. Duplicated swabs (N = 102) were taken from the vaginal fornix of cows to perform aerobic and anaerobic cultures as well as conventional biochemical tests. Out of 102 swabs, bacterial growth was obtained in 55 (53.9%) while the remaining 47 (46.1%) did not exhibited any bacterial growth. Of the 55 bacterial growths, 23 (41.8%) were aerobic whereas 32 (58.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 13 publications
0
16
1
1
Order By: Relevance
“…Dominant bacteria phyla, Firmicutes and Bacteroidetes, for instance, in the 6‐month group were similar to those in the female parent group, indicating maternal influence on the gut microbiome. The first bacterial encounter occurs during the birthing process, where Firmicutes and Bacteroidetes are the predominant phyla in the vaginal cavity . Significant differences in the fecal flora structure indicated that fecal microbiome diversity after 6 months was changed unpredictably.…”
Section: Discussionmentioning
confidence: 97%
“…Dominant bacteria phyla, Firmicutes and Bacteroidetes, for instance, in the 6‐month group were similar to those in the female parent group, indicating maternal influence on the gut microbiome. The first bacterial encounter occurs during the birthing process, where Firmicutes and Bacteroidetes are the predominant phyla in the vaginal cavity . Significant differences in the fecal flora structure indicated that fecal microbiome diversity after 6 months was changed unpredictably.…”
Section: Discussionmentioning
confidence: 97%
“…An examination of vaginal bacterial community structure has been conducted in several species including humans (Ravel et al 2011; Jin et al 2007; Kim et al 2009), Rhesus macaques (Spear et al 2010), and Criollo Limonero cows (Zambrano-Nava et al 2010). These studies illustrate the differences in bacterial species composition across a functionally and anatomically similar structure.…”
Section: Discussionmentioning
confidence: 99%
“…Rare outbreaks with a large number of mortalities have involved avian hosts (Wolcott, 2007), or mice (Wayson, 1927), whereas mortalities in wild ungulates were previously limited to small numbers (Bruner et al, 1984; Campbell et al, 1994). Both cattle (Hassanein et al, 2003; Zambrano-Nava et al, 2011) and swine (Stephenson and Berman, 1978) can act as asymptomatic carriers, with E. rhusiopathiae isolated from tonsils, bone marrow (Spears, 1955), and other tissues at slaughter of apparently healthy animals, and it is also part of the normal vaginal flora of cattle (Zambrano-Nava et al, 2011). Erysipelothrix rhusiopathiae appears to have a particular tropism for tonsils; tonsillar crypts are a likely port of entry and site for persistent infection in swine (Harada et al, 2013).…”
Section: Introductionmentioning
confidence: 99%